Mengapa Anak Sulit Fokus? Analisis Faktor Konsentrasi Belajar Anak Usia Dini - Mulyo, Zavira Nisa Awanda (UIN Sultan Maulana Hasanudin Banten, 2026)
in practice, many children still have difficulty maintaining focus during learning activities. This study aims to analyze the factors influencing the concentration in learning of 5–6-year-old children in class B2 of Al-I'Dad An Nuur Kindergarten, Sleman. The study used a descriptive qualitative approach with 15 children as subjects. Data collection techniques included observation, interviews, and documentation. Data were analyzed using interactive analysis techniques through data reduction, data presentation, and conclusion drawing. The results indicate that children's concentration in learning is influenced by the child's physical condition, morning motor activity, the use of varied learning methods, the use of ICT media, parenting styles, the intensity of mobile phone use, home learning discipline, and communication between parents and children. Children tend to focus better when learning is presented in an active, fun, and engaging manner, while excessive exposure to gadgets and a lack of learning habits at home make children more easily distracted during learning. This study emphasizes the importance of collaboration between schools and families in creating a supportive learning environment to support the development of concentration in early childhood learning.